2017
DOI: 10.1371/journal.pone.0190316
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an extreme climatic disturbance and different fertilization treatments on plant development, phenology, and yield of two cultivar groups of Solanum betaceum Cav.

Abstract: Changing climatic conditions impose a challenge both to biodiversity and food security. The effects of climate change affect different aspects of the plant or crop, such as morphological and phenological aspects, as well as yield. The effects of greenhouse conditions might be comparable in some cases to a permanent extreme disturbance in climate and weather, thus, contributing to our knowledge on climate change impacts on plant species. We have investigated the differences for 23 traits in two cultivar groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…It is well-known that other climatic factors, such as moisture balance and extreme temperature events, also determine plant distribution [67][68][69]. Numerous studies have shown that local moisture balance and extreme temperature events will affect the physiological characteristics of plants, such as yield, florescence, and tolerance [70,71]. Under the climate change, biochemical interaction will also affect the adaptability of species to the environment [72][73][74].…”
Section: The Influence Of Major Variables On Adaptationmentioning
confidence: 99%
“…It is well-known that other climatic factors, such as moisture balance and extreme temperature events, also determine plant distribution [67][68][69]. Numerous studies have shown that local moisture balance and extreme temperature events will affect the physiological characteristics of plants, such as yield, florescence, and tolerance [70,71]. Under the climate change, biochemical interaction will also affect the adaptability of species to the environment [72][73][74].…”
Section: The Influence Of Major Variables On Adaptationmentioning
confidence: 99%
“…Tree tomato pulp has been documented to contain various components such as dietary fibre, starch, soluble sugars (sucrose, glucose and fructose), organic acid (e.g., malic and citric acids), vitamins (e.g., C, B2, B6, and E), phenolic compounds (e.g., anthocyanins, chlorogenic acid, hydroxycinnamic acid), carotenoids (e.g., β-carotene, lutein), terpenoids, steroids, saponins, alkaloids, tannins, proteins, essential amino acids (e.g., glutamic acid, leucine, serine, aspartic acid, and glycine) and minerals (e.g., potassium, phosphorus, calcium, magnesium, iron, copper and zinc) [ 5 , 6 ]. However, the phytochemical composition and fruit quality of tree tomatoes are influenced by various genetic and environmental factors such as light, altitude, temperature, water availability, pre-harvest conditions, rootstock, crop load, fruit position within the tree, cultural practices, and industrial processes [ 1 , 4 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that other climatic factors, such as moisture balance and extreme temperatures, determine plant distribution (Stephenson 1990;Widrlechner et al 2012;Zhang et al 2020). Several studies report the effect of moisture and extreme temperatures on the physiological characteristics of plants, such as growth, yield, flowering and tolerance (Tandazo-Yung et al 2017;Song et al 2018).…”
Section: Discussionmentioning
confidence: 99%